DETERMINATION OF THE PERCENTAGE OF MICRO AND MACRO ELEMENTS IN THE TANACETUMVULGARE PLANT - Abdimalikov Ibodullokhan Ibragimovich; Rakhmonova Sabakhat Ziyodulloevna; Khujanazarov Shukhrat; Bozorov Ogabek Talib ugli (Zeta Repository, 2023)
In this article, the elements and their compounds contained in the powder of the ground part of the Tanacetum Vulgare plant were determined in percentages, and information about their chemical composition and use in medicine is presented.